2018
DOI: 10.1002/jssc.201701175
|View full text |Cite
|
Sign up to set email alerts
|

Dereplication‐guided isolation of a new indole alkaloid triglycoside from the hooks of Uncaria rhynchophylla by LC with ion trap time‐of‐flight MS

Abstract: Uncaria rhynchophylla (Gou-Teng) as the monarch herb of many formulae (Fufang), e.g. "Tian-Ma-Gou-Teng-Yin," "Ling-Jiao-Gou-Teng-Yin," and "Yi-Gan-San", is a famous traditional Chinese medicine documented in the Chinese pharmacopoeia for mental and cardiovascular diseases. In the traditional Chinese medicine system, only the hook-bearing stems are used as the crude materials for Gou-Teng, and the hooks are always considered more effective than the stems. Focusing on the mono-herb and its active constituents fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In addition, Zhang et al reported that the extracts of different UR species also displayed agonistic effects on melatonin receptors [ 99 ]. Several new alkaloids isolated from UR show agonistic activities on both MT1 and MT2 melatonin receptors [ 100 , 101 ]. The increase in melatonin signaling by these UR components may confer inhibitory signal to the active trigeminal nerve and further suppress the abnormal release of CGRP.…”
Section: The Effects Of Ur Components On 5-ht and Melatonin Signalingmentioning
confidence: 99%
“…In addition, Zhang et al reported that the extracts of different UR species also displayed agonistic effects on melatonin receptors [ 99 ]. Several new alkaloids isolated from UR show agonistic activities on both MT1 and MT2 melatonin receptors [ 100 , 101 ]. The increase in melatonin signaling by these UR components may confer inhibitory signal to the active trigeminal nerve and further suppress the abnormal release of CGRP.…”
Section: The Effects Of Ur Components On 5-ht and Melatonin Signalingmentioning
confidence: 99%
“…Indole alkaloids are the characteristic constituents in Uncaria plants with high response in positive mode MS. In this investigation, a number of 35 indole alkaloids were described and divided into six subclasses including cadambine-type (19, 21, 23, 26, 47), vinsosamide-type (15), D-seco-type (18, 25, 33, 38, 44, 50), corynoxine-type (11,20 , 22, 24, 27, 28, 31, 32, 34, 35, 36, 37, 42), corynantheintype (40, 43, 45, 48, 51, 53, 55, 57), and ajmalicine-type (39,54). In accordance with the previous investigation [17], D-seco alkaloids commonly generated the characteristic fragmentation ions ascribed to the loss of 17 Da (NH 3 ) in the MS 2 experiment; the indole and oxindole alkaloids could be differentiated from their respective maximal UV absorptions around 280 nm (indole) or 240 nm (oxindole); the numbers and types of glycosyl moieties were determined by the mass defects between the parent and fragment ions.…”
Section: Indole Alkaloidsmentioning
confidence: 99%
“…In the positive MS 2 experiment, the sequential losses of three glycosyl moieties (C 6 H 10 O 5 , 162 Da) suggested the presence of three glucosyl in the structure. Finally, this compound was isolated under the guidance of LCMS analysis, and identified to be 2′-O-[β-d-glucopyranosyl-(1 → 6)-β-d-glucopyranosyl]-11hydroxyvincosamide based on rigid 1D and 2D NMR spectroscopic data [20].…”
Section: Indole Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkaloids, triterpenoids, flavonoids and organic acids are the main constituents in U. rhynchophylla [8]. Our previous study disclosed that different parts of U. rhynchophylla could be well differentiated by their chemical profiles [9], from which two pairs of dimeric isoechinulin-type alkaloids [10], two flavanols [11], and one indole alkaloid triglycoside [12] with antidepressant potency were isolated under the guidance of bioassay. As a comparison, the antidiabetic constituents of U. rhynchophylla have been little investigated.…”
Section: Introductionmentioning
confidence: 99%